The Impact of COVID-19 Pandemic on Corporate Social Responsibility and Job Embeddedness in China - Meirun, Tang; Lockey, Steven; Blenkinsopp, John; Yueyong, He; Ling, Ling (Frontiers in Psychology, 2022)
This article aims to investigate the impact of employee perceptions of corporate social responsibility (CSR) on job embeddedness under the drastic circumstances of coronavirus disease 2019 (COVID-19). This study also investigated the role of organizational identification as a psychological mechanism linking employee perceptions of corporate social responsibility (CSR) to job embeddedness. Survey data were collected from 325 employees in the banking industry of China and analyzed using partial least squares structural equation modeling (PLS-SEM). Results revealed that CSR to employees and organizational identification was positively and significantly related to job embeddedness, while CSR to customers, CSR to government, and CSR to society did not significantly predict job embeddedness. Organizational identification fully mediated the relationship between CSR to customers, CSR to government, CSR to society, and job embeddedness, and partially mediated the relationship between CSR to employees and job embeddedness. The results suggest engaging in CSR activities can lead employees to identify themselves with the organization and enhance their embeddedness. The article concludes with several implications for practice and recommendations for future research.